Застосування даних СІЧ-2 для остаточного визначення пожеж,особливості їх оброблення та спільного використання з даними MODIS (TERRA) та AVHRR (NOAA) - Вишняков, В.Ю. (Екологічна безпека та природокористування, 2012)
In the article the features of data processing "Sich-2" and sharing of data MODIS (TERRA) and AVHRR (NOAA) within the final determination of the fires on the territory of Ukraine. Presented algorithms determine fires according to NOAA and Sich-2 using GIS. Defined method of processing and interpretation of data «Sich-2», within the monitoring fires in Ukraine.